2022
DOI: 10.1017/jbr.2021.188
|View full text |Cite
|
Sign up to set email alerts
|

Youth Sexuality, Responsibility, and the Opening of the Brook Advisory Centres in London and Birmingham in the 1960s

Abstract: This article takes the opening of the Brook Advisory Centres in London (1964) and Birmingham (1966) as a comparative case study for exploring the public debate on youth sexuality. The two centers were the first in postwar Britain specifically dedicated to the provision of advice on birth control and emotional problems to unmarried and young people. By focusing on an initiative that launched amid rising concerns over illegitimacy and promiscuity, the article engages with the debate over social change in the 196… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…More recent historical scholarship disputes these claims. Rusterholz (2019Rusterholz ( , 2021Rusterholz ( , 2022 has shown that mid-century sexual counselling called on individuals to work actively, stoically and responsibly towards achievement of the emotional openness perceived as necessary to mutual sexual satisfaction in stable heterosexual relationships. This research confirms and extends the analysis of Chettiar (2016), who sees the state-sponsored expansion of marriage counselling and debates on divorce reform as two sides of the same coin; both demonstrate the identification of romantic and sexual relationships, underpinned by psychologised concepts of emotional health, as essential to social stability.…”
Section: Original Researchmentioning
confidence: 99%
“…More recent historical scholarship disputes these claims. Rusterholz (2019Rusterholz ( , 2021Rusterholz ( , 2022 has shown that mid-century sexual counselling called on individuals to work actively, stoically and responsibly towards achievement of the emotional openness perceived as necessary to mutual sexual satisfaction in stable heterosexual relationships. This research confirms and extends the analysis of Chettiar (2016), who sees the state-sponsored expansion of marriage counselling and debates on divorce reform as two sides of the same coin; both demonstrate the identification of romantic and sexual relationships, underpinned by psychologised concepts of emotional health, as essential to social stability.…”
Section: Original Researchmentioning
confidence: 99%
“…But as we see in Elizabeth's work, historical efforts to raise awareness through education became a 'constant battle' for young people asserting their agency and rights. Indeed, it was one of many battles fought over the sexuality of young people in the face of rapid social change, affecting their access to education and health services (Rusterholz, 2021). And these battles still rage, not just over the place of Relationship and Sex Education in schools, but also the autonomy of trans adolescents.…”
Section: Hiv/aids Amr and Ongoing Challengesmentioning
confidence: 99%
“…Moreover, while significant interventions by Eleanor O’Leary and Carole Holohan have shed light on youth culture in 1950s and 1960s Ireland respectively, we still know very little about young people’s experiences of sexual health in Ireland in the later twentieth century (Holohan 2018; O’Leary 2018). In the British context, scholars such as Caroline Rusterholz and Hannah Elizabeth have conducted valuable work in broadening our understandings of the controversies around young people’s sexual health and the development of sexual health services and education aimed at young people (Rusterholz (2021, 2021); Elizabeth 2021).…”
mentioning
confidence: 99%